The social-cognitive determinants of calcium intake for preventing osteoporosis in women in Isfahan: A cross-sectional study using path analysis - Mahin Nematollahi; Ahmad Ali Eslami (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Osteoporosis is a common disease in women over age 45 years. Calcium intake is among the factors that help prevent osteoporosis. Identifying the social-cognitive determinants of calcium intake can have a major role in the development of osteoporosis prevention programs. MATERIALS AND METHODS: This cross-sectional study was conducted on 400 women aged <50 years from 10 health centers by cluster sampling in Isfahan in 2016. A hypothetical social-cognitive model was assessed using path analysis, and the fit indices and explanatory power of the model were assessed. The constructs, including self-efficacy, outcome expectations, social support, and self-regulation, were taken as the explanatory variables and calcium intake as the criterion variable. RESULTS: The mean age of the participating women was 34.07 years (standard deviation = 7.99) (range = 19-50), and their mean calcium intake was reported as 909.94 (12. 6) mg/day. The conceptual model was able to explain 73% of the variance in calcium intake and had good fit indices. Self-regulation was identified as the strongest predictor of calcium intake, and outcome expectation was eliminated from the model since it was the weakest explanatory factor of calcium intake. CONCLUSIONS: The theoretical model of this study is recommended as a suitable framework for the development of targeted osteoporosis prevention interventions.